Design Inverter SPWM Tow Frequency Based Soil Moisture Sensor Using Arduino - Rajagukguk, Antonius; Kurniawan, Riski (International Journal of Electrical, Energy and Power System Engineering, 2021)
Inverters on induction motor control are widely used both in industry, transportation, household, and agriculture. This inverter is designed to convert Direct Current electricity into Alternating Current electricity. In this study, the inverter is designed using the Sinusoidal Pulse Width Modulation (SPWM) switching method and is able to produce pure sine waves of two frequencies of 50 Hz and 25 Hz with input control based on the reading of the soil moisture sensor. The purpose of this research is to apply to the controller of automatic watering plants. This system uses Arduino Uno as a SPWM signal generator and processes the reading of the soil moisture sensor and controls the LC filter. Based on the test results of the inverter control system, it is obtained an output voltage of 200 volts with a measured frequency of 48.83 Hz and 24.61 Hz with an input voltage of 12 Volt DC. The inverter system when loaded with single phase induction motors obtained efficiency at a frequency of 50 Hz by 36% and at a frequency of 25 Hz obtained by 70%. Thus, it can be concluded that this single-phase inverter can be used for applications in single phase induction motor speed control.